Intestinal Schwannoma: A Clinicopathological, Immunohistochemical, and Prognostic Study of 9 Cases - Zhenbo Shu; Chunsheng Li; Mingze Sun; Zhongmin Li (Gastroenterology Research and Practice)
Background. Intestinal schwannoma is a type of intestinal interstitial tumor with a very low incidence. At present, there are few studies on intestinal schwannoma. Methods. From January 2010 to January 2018, the patients diagnosed with intestinal schwannoma at the China-Japan Union Hospital of Jilin University were retrospectively reviewed. The patients’ clinicopathological features and prognosis were analyzed. Results. This study enrolled 9 patients with intestinal schwannoma, including 3 males and 6 females. The main symptoms of the patients were abdominal pain and melena. Abdominal computed tomography showed intussusception, slightly high-density shadowing in the intestine, thickening of the intestinal wall, and an intestinal mass. Colonoscopy and endoscopic ultrasonography showed submucosal masses without ulcer formation. Two patients underwent endoscopic biopsy, and the pathological results revealed inflammation and necrosis. One patient had increased neuron-specific enolase (NSE) levels. Immunohistochemical analysis showed that the tumor cells were positive for S-100 and negative for CD117, DOG-1, desmin, and smooth muscle actin. An average of 17 lymph nodes were found around the intestines in 4 patients, all of which demonstrated reactive hyperplasia. No recurrence or metastasis occurred during postoperative follow-up. Conclusions. Intestinal schwannoma is a rare tumor, and in our study its incidence was higher in women than in men. The main symptoms were abdominal pain and melena. Preoperative increases in NSE levels might contribute to a diagnosis. Complete surgical resection with free negative margins is the standard treatment for benign schwannoma. There was no recurrence or metastasis after complete surgical resection, suggesting that follow-up may not be required.